2011
DOI: 10.1242/dev.069625
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between FGF2 and BMP controls the self-renewal, dormancy and differentiation of rat neural stem cells

Abstract: Results Establishment of rat foetal NS cell culturesWe followed the protocol established for foetal mouse tissue described in Conti et al. (Conti et al., 2005). Dissociated cells from E13.5 rat foetal cortex or spinal cord were plated onto laminincoated tissue culture plastic in medium supplemented with FGF2 and epidermal growth factor (EGF). Many cells attached within 24 hours. The primary cultures were heterogeneous; they contained nestin-positive precursor cells, TuJ1-positive neurons and a small Summary Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Analysis of the gene expression profile of cell cycle-arrested NS cells showed that these cells are very significantly enriched for genes induced by fibroblasts and different types of adult tissue stem cells when they enter quiescence, thus suggesting that different cell types, including NS cells, employ overlapping quiescence gene expression programs. In contrast, these cells were not significantly similar to parenchymal astrocytes, in agreement with a recent report showing that while BMP signaling alone promotes terminal astrocytic differentiation, exposure to both BMP and FGF2 maintains the stem cell character of NS cells (Sun et al 2011). …”
Section: An In Vitro Model Of Nsc Quiescencesupporting
confidence: 89%
See 3 more Smart Citations
“…Analysis of the gene expression profile of cell cycle-arrested NS cells showed that these cells are very significantly enriched for genes induced by fibroblasts and different types of adult tissue stem cells when they enter quiescence, thus suggesting that different cell types, including NS cells, employ overlapping quiescence gene expression programs. In contrast, these cells were not significantly similar to parenchymal astrocytes, in agreement with a recent report showing that while BMP signaling alone promotes terminal astrocytic differentiation, exposure to both BMP and FGF2 maintains the stem cell character of NS cells (Sun et al 2011). …”
Section: An In Vitro Model Of Nsc Quiescencesupporting
confidence: 89%
“…BMP signaling promotes quiescence in not only NS cell cultures (Mira et al 2010;Sun et al 2011; this study), but also the adult hippocampus, where perturbation of BMP signaling results in excessive proliferation and eventual depletion of hippocampal stem cells (Mira et al 2010). BMPs have also been implicated in the quiescent state of other types of adult stem cells, including hair follicle, intestinal, and hematopoietic stem cells (Kobielak et al 2007;Li and Clevers 2010;Lien et al 2011).…”
Section: Bmp Signaling and Quiescencementioning
confidence: 77%
See 2 more Smart Citations
“…To address this question, we treated NS cells with three different growth factor regimes to induce cell cycle exit and stimulate differentiation or quiescence, and we used microarrays to detect significantly up-and down-regulated genes. We used BMP4 to induce astrocytic differentiation (Sun et al 2011a), treatment with B27-and FGF2-containing medium to induce an early neuronal progenitor fate (Spiliotopoulos et al 2009), and BMP4 + FGF2 to induce NS cell quiescence (Sun et al 2011a;Martynoga et al 2013). In all three experiments, 1340-2054 genes were significantly down-regulated and 1442-2054 genes were up-regulated, showing the extent of transcriptional rewiring.…”
Section: Different Cre Classes Associate With Genes That Are Regulatementioning
confidence: 99%